(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2015)
In 1982, in the journal “International Organization”, was published a special issue on international regimes. This special edition was reprinted a year later as a collective book under the direction of Stephen D. Krasner titled International Regimes. This book aims to be the echo of the existing theoretical debate within the discipline of International Relations during this period namely the analysis of international regimes in the light of realism and liberalism. Clustered around these two theoretical trends, the authors of this book, with the exception of Susan Strange, tried to support each of their side the merits of their theory to explain the conditions for the creation, maintenance and change of an international regime. As for Strange, she criticizes the analysis of schemes considers a transient, vague fashion, value-laden, too static and state-centred. Given the changes experienced by the theory of schemes over the past 30 years, we hypothesize that some criticisms of Strange always remain relevant while others are less relevant or not at all relevant.